Necrotizing Fasciitis in a Leprosy Patient - Nie Nie; Augustine Natasha; Sweety Pribadi; Yulia R. Saharman; Chairunissa T. Rizal; Anis Karuniawati; Pratiwi Sudarmono (eJournal Kedokteran Indonesia, 2022)
Leprosy is an infection caused by Mycobacterium leprae. Disability after the infection is common  and necrotizing fasciitis could deteriorate the patient current condition. We present the case of necrotizing fasciitis of the right limb inpatient with tarsal disintegration and plantar ulcer due to previous leprosy infection.  The microbiology culture was inadequate in the early stage of management, which delayed the definitive  antibiotic for patient and the progressive necrotic infections were uncontrolled. Amputation was done to save the patient’s life and the latter microbiology culture was able to determine the definitive antibiotic therapy. This report highlights the needs of disability management and infection control for leprosy patient after the treatment is completed.